PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS V SEKOLAH DASAR - Santi Sopianti Sri Mulya, - (2022)
This study aims to describe the effect of using the Project Based Learning model on the creative thinking ability of students on the material of changing the shape of objects in the fifth grade of elementary school. The background of this research is the demand for 21st century education to be able to think creatively, especially in learning natural sciences in stimulating curiosity and developing creative thinking skills in finding ideas and solving problems. Shown by the use of learning models that are less varied and practicum activities that are not paid attention to by the teacher. This study uses the Quasi Experiment Design method with data collection using test instruments (pretest and posttest) and structured observation. The sample in this study was the fifth grade students of SDN 1 Sindangkasih, Ciamis district with purposive sampling technique. Class VA as an experimental class with 20 students and class VB as a control class with 20 students. Based on the results of data analysis using the Mann-Whitney test, a gain score of 0.001 <0.05. It can be concluded that the use of the PjBL can improve students' creative thinking skills in material changing objects and is better than the use of conventional models in elementary schools. Keyword: Project Based Learning, Creative Thinking Ability